(untitled) (Medico Legal Update, 2019)
Objectives: Embelin has been used in various treatments for skin diseases have excellent efficacy and have been widely used in folk remedies. Therefore, we want to observe the possibility of embelin as an additive to cosmetics. Method: The cytotoxicity test was conducted to observe the safety of the component, and the antioxidant force of the component itself was observed using a DPPH solution. The effects on ROS generation using DCFDA were observed. We observed the potential as a inhibitor of NO produced by inflammatory reactions and measured tyrosinase activity and melanin production to observe the possibility of utilization as skin whitening. Findings: The results of observing the decimals using DPPH showed weak inhibition due to be weakly suppressed. Antioxidants were observed using Raw 264.7 macrophage. It inhibited ROS production in the cells induced by silica. In particular, production was inhibited on a concentration-dependent basis. As a result, the embelin has its own antioxidant function, has been shown to act as antioxidant in cells, and its concentration has inhibited NO production. Although the tyrosinase activity using L-dopa and L-tyrosine as substrates did not have any significant effect, melanin production in melanin cells resulted in concentration - dependent suppression. Applications: Based on these results, it was found that embelin was highly antioxidant and was likely to be used as an anti-aging cosmetics ingredient.